A career in theoretical physics - Anderson, P. W (World Scientific, 1994)
Includes bibliographical references; This unique volume presents the scientific achievements of Nobel laureate Philip Anderson, spanning the many years of his career. In this new edition, the author has omitted some review papers as well as added over 15 of his research papers. As in the first edition, he provides an introduction to each paper by explaining the genesis of the papers or adding some personal history. The book provides a comprehensive overview of the author's work which include significant discoveries and pioneering contributions, such as his work on the Anderson model of magnetic impurities and the concept of localization; the study of spin glasses, the fluctuating valence problem and superexchange; his prediction of the existence of superfluidity in He3; his involvement in the discovery of the Josephson effect; his discovery of the â€œHiggsâ€ mechanism in elementary particle physics; and so on